1978
DOI: 10.1083/jcb.78.2.r28
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in the production of specific cellular peptides during the growth of animal cells.

Abstract: Patterns of newly synthesized proteins of Vero cells in different growth states were obtained using two-dimensional gel electrophoresis. The 240 most prevalent peptide spots were then compared. Cells in exponential growth and in the stationary phase were found to have patterns of peptide spots characteristic of their state of growth. The transition between these patterns is progressive, and the cells acquire a pattern characteristic of quiescent ceils by the late exponential phase. These observations suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1979
1979
1983
1983

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Spot intensities on two gels containing two different samples exposed for the same period of time (72 h) were compared, and the obvious differences in the intensity of spots were observed visually. To confirm the results obtained by visualization of gels, we exposed two gels containing two different samples for different periods of time by analyzing the length of exposure required before a peptide spot became visible, as previously described (15). The spots differing in intensity according to the first technique were found to be the same and to differ by at least 8-fold by the second technique.…”
Section: Double Gel Electrophoresismentioning
confidence: 87%
See 1 more Smart Citation
“…Spot intensities on two gels containing two different samples exposed for the same period of time (72 h) were compared, and the obvious differences in the intensity of spots were observed visually. To confirm the results obtained by visualization of gels, we exposed two gels containing two different samples for different periods of time by analyzing the length of exposure required before a peptide spot became visible, as previously described (15). The spots differing in intensity according to the first technique were found to be the same and to differ by at least 8-fold by the second technique.…”
Section: Double Gel Electrophoresismentioning
confidence: 87%
“…The synthesis of these 14 new peptides may reflect a direct effect of the growth factors on the pattern of newly synthesized proteins once cultures become confluent. Previous studies done with bovine vascular endothelial cells (22) and Vero cells (15) have indicated that cells will synthesize more peptides in their logarithmic growth phase than when confluent and resting. In contrast, the bovine granulosa cells derived from smallsized follicles synthesized more peptides at confluence than when actively growing.…”
Section: Discussionmentioning
confidence: 99%
“…After this time, the labeled medium was removed and the cells were rinsed three times with 2 ml of ice cold phosphate buffered saline (PBS). After the last wash, the cells were solubilized by the addition of 0.3 ml of lysis buffer (9.5 M urea, 2% w/v NP 40,1.6% ampholines, pH 3.5-10, and 5% p-mercaptoethanol) to the culture plates (Lee and Engelhardt, 1978). The lysate was then used directly for two-dimensional polyacrylamide gel electrophoresis, using the procedure described by O'Farrell(1975) as modified by Lee and Engelhardt (1978).…”
Section: Chemicalsmentioning
confidence: 99%
“…After the last wash, the cells were solubilized by the addition of 0.3 ml of lysis buffer (9.5 M urea, 2% w/v NP 40,1.6% ampholines, pH 3.5-10, and 5% p-mercaptoethanol) to the culture plates (Lee and Engelhardt, 1978). The lysate was then used directly for two-dimensional polyacrylamide gel electrophoresis, using the procedure described by O'Farrell(1975) as modified by Lee and Engelhardt (1978). Ampholines, pH 5-8 and pH 3.5-10, were used for isoelectric focusing in the first dimension and 10% polyacrylamide gels were used in the second dimension.…”
Section: Chemicalsmentioning
confidence: 99%
“…This system separates polypeptides in the first dimension by charge and in the second dimension by subunit molecular size. It can resolve several hundred polypeptides from proteins present in biological samples and has been used by many workers to study complex cellular phenomena, such as changes in polypeptide synthesis during cell growth (Lee and Engelhardt, 1978) or following various events, such as neoplastic transformation (Hirsch et aL, 1978;Takami and Busch, 1979), viral transformation (Strand and August, 1977), hormonal treatment (Ivarie and O'Farrell, 1978;Garrels and Schubert, 1979) and cell differentiation (Vermorken and Bloemendal, 1978).…”
mentioning
confidence: 99%